2018
DOI: 10.1016/j.scitotenv.2018.02.069
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the 87Sr/86Sr from rocks and soils to vine and wine: An experimental study on geologic and pedologic characterisation of vineyards using radiogenic isotope of heavy elements

Abstract: In this paper we report an experimental study to assess the process of Sr-isotope uptake from the soil and its transfer to the grapevine and then to the wine made through micro-vinification. The experimental work has been carried out with a deep control of the boundary conditions (i.e., type of soil, geologic substratum, ground water supply, etc.) on 11 selected vine-plant sites over a period of four harvest years. Sr-isotopes have been determined on grape-bunches, grapevine sap, on the bioavailable fraction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…The best match of 87 Sr/ 86 Sr ratio of tested samples is at third and fourth decimal place. The match was getting worse when the product of vine were compared with bulk soil or rock [1,8].…”
Section: Strontium As Trace Elementmentioning
confidence: 99%
“…The best match of 87 Sr/ 86 Sr ratio of tested samples is at third and fourth decimal place. The match was getting worse when the product of vine were compared with bulk soil or rock [1,8].…”
Section: Strontium As Trace Elementmentioning
confidence: 99%
“…Despite both light and heavy isotopes are almost able to establish a direct link between the geographic area, in which the plant's life cycle is active, and the finished product, the use of the latter ones offers several advantages. In particular, heavy elements do not show a significant fractionation during the plant uptake process making possible to develop stable models over time [8]. Recently, there has been renewed interest in the descriptive capacity of strontium demonstrating the potentials of this isotopic signature in the agri-food field [9].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, both aspects related to the influence of the soil size distribution on the isotopic data and the effectiveness of the Rb mathematical correction have been tackled. Furthermore, a preliminary study was carried out in order to verify whether the Sr isotopic ratio coming from vine branches can be a more distinctive geographical traceability tool for the Chianti Classico wine production areas, as other studies on the provenance have shown [10,18,22].…”
Section: Introductionmentioning
confidence: 99%
“…For a statistical approach to the geographical origin of food, a large dataset of precise and accurate values is needed in order to evaluate the indicator variability range of both the food and the soils and to build robust classification models [18].If, on the one hand, it is a quite simple task to collect isotopic ratios data for the food matrix, on the other hand, the interpretation of the data from the soil is complex [19][20][21]. In fact, depending on the geology of the territory, the 87 Sr/ 86 Sr ratio could vary considerably as a function of many variables difficult to evaluate a priori [22,23]. Probably, the discrepancy between the bioavailable fraction and the total amount of strontium in a soil could represent the limiting factor for the construction of reliable geographical traceability models for food.The possibility of discriminating between samples' origins for geographical traceability purposes often lies at the 4th or 5th decimal places of this isotopic ratio.…”
mentioning
confidence: 99%
See 1 more Smart Citation